The Mediation Effects of Tax Avoidance between ESG And Cost of Debt, Firm Value: Evidence from ASEAN Listed Corporations - Duong, Thi-Quynh; Huang, Yu-Chuan (Journal of Entrepreneurship, Business and Economics, 2022)
The object of this research is to explore whether environmental, social, and governance (ESG)  activities have an influence on capital structure, tax avoidance, and firm value in the context of Southeast Asia. Also, examining whether existing two mediating effects of corporate tax avoidance between ESG activities and the cost of debt, and between ESG activities and firm value. The researchers applied regression models and the Sobel test with a total of 1105 samples that are existing listed companies reporting ESG on the Refinitiv data stream from 2018-2021. The results pointed out that ESG has a positive significant impact on tax avoidance, firm performance, and the debt of the firm. It also showed a positive correlation effect between tax avoidance and the value of the firm. Tax avoidance plays a partial mediation role between ESG and firm value. Therefore, research findings contribute to the related literature and associated partitioners and investors could apply the results for managing corporations and understanding corporations’ operating strategies in the ASEAN region. Research paper Keywords: Environmental, Social, and  Governance (ESG); Tax avoidance; Firm value; Cost of debt Reference to this paper should be made as follows: Duong, T., & Huang, Y. (2022). The Mediation Effects of Tax Avoidance between ESG And Cost of Debt, Firm Value: Evidence from ASEAN Listed Corporations. Journal of Entrepreneurship, Business and Economics , 10 (2S2), 201–232.